Ethnic touristic islands - Rémy Tremblay (Via@)
In this article, we show how a touristic destination can transform into an ethnic touristic island. Drawing on a case study of the Quebecois in Florida, we propose a model that explores a process developed by the American researcher Dallen Timothy. The model has three stages: adoption of the destination, its transformation into an ethnic touristic island and its subsequent decline.tourism, transnational community, Floribec, Quebecois in Florida